KEANEKARAGAMAN KARAKTER TANAMAN KELAPA (Cocos nucifera L. ) YANG DIGUNAKAN SEBAGAI BAHAN UPACARA PADUDUSAN AGUNG - Kriswiyanti, Eniek (Jurnal Biologi Udayana, 2013)
The study was aimed to identify the characteristic variations of the coconuts ( Cocos nucifera L.) trees that are used as materials for the Padudusan Agung ceremony in Bali . Exploration, interview , and observation of character variations of coconuts have been conducted from coconut plantation area from each regency in Bali. The characteritations was identified based on measurements and observations of parts of plant according to “Discriptors for Coconuts”. The result shows that there was a narrow variation on the stem and leaf characters (2.81-11.83%), while high variations found on the fruit numbers in a bunche for the generative characters (42.8%). Padudusan Agung ceremony uses eleven types (cultivars) of coconuts. Those are: gadang, gading, bulan, and surya with green, yellow, white, red epicarpium colours respectively. Young fruit of Udang coconuts have red mesocarpium, sudamala has double spathas, bingin has root grown on stem, be julit has plicated primordium leaves, bojog has hush likes the color of monkey hairs, ancak has branched stem, and rangda has petiole twisted on the top of the stem.
Keywords: Cocos nucifera L., padudusan agung, mesocarpium, spatha, twisted